(untitled) (Universal International Scientific Journal, 2026)
It studies the possibilities, methods and effectiveness of creating innovative pedagogical content using generative artificial intelligence technologies. In a modern educational environment, individualization of educational materials, increasing student interest and saving teachers’ time are among the most pressing issues. As part of the research work, mechanisms for developing lesson plans, practical tasks, visual-didactic materials and assessment criteria using neural networks specialized in creating text, images and multimedia were analyzed.